Telecentres: Support at the centre - Agbenyo, Stephen; Ken Kubuga, Ken; Koopman, Martine (Technical Centre for Agricultural and Rural Cooperation, 2012)
In the years since they were first established, Ghana's community information centres have faced a wide range of challenges as they bring ICTs to rural communities. With the help of specialist advisers, many of those problems have been overcome